Entrepreneurial Orientation, Marketing Capacity, and Business Performance of Homestays in Priority Destinations: The Mediating Role of Sustainable Competitive Advantage - Riko Fridolend Sianturi; Esli Silalahi; Betniar Purba (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study investigates the direct and indirect determinants of homestay business performance, specifically examining the interrelationships among entrepreneurial orientation, tourist village marketing capacity, sustainable competitive advantage, and overall business performance. Utilizing a quantitative approach with a descriptive statistical design, data were collected from a sample of 192 homestay owners in the tourist villages surrounding Lake Toba through quota sampling. The data were analyzed using Structural Equation Modeling (SEM) via SmartPLS software. The empirical results demonstrate that entrepreneurial orientation and local marketing capacity significantly and directly enhance immediate homestay business performance. However, sustainable competitive advantage (SCA) exhibited a negative relationship with immediate business performance. This indicates a competitive mediation and an investment trade-off dynamic; short-term performance metrics may initially decline as homestay owners prioritize long-term sustainable advantages over aggressive short-term sales. Furthermore, cultural values did not significantly moderate the relationships between the independent variables and business performance. While entrepreneurial orientation and local marketing capacity remain the predominant direct drivers of operational success, building sustainable competitive advantage requires strategic long-term investments that may temporarily dampen immediate financial gains. Policymakers and local stakeholders should focus on providing practical marketing skills and structural business support to foster resilient rural tourism ecosystems.